EL PROYECTO DEL NUEVO TEATRO DE MURCIA DE D. VENTURA RODRÍGUEZ (1798) - Pina Caballero, Cristina I. (Imafronte, 1999)
In 18th century theatre was the mose important entertaiment in the main towns and Murcia wasn 't an exception. this article deals with a proyect of Ventura Rodriguez in 1798 for the construction of a new theatre in Murcia, that had replace the old "casa de comedias" near the Bull's Gate. This is the hisiory of a long process that never became to the end because the theatre wasn't buided. It was many determining factors, but the most important was the high cost of a new structure.